The storm runner ebook - Cervantes, J.C (Storm Runner, 2018)
A contemporary adventure based on Maya mythology from Rick Riordan Presents and New York Times bestselling author J. C. Cervantes! Zane has always enjoyed exploring the dormant volcano near his home in New Mexico, even though hiking it is challenging. He'd much rather hang out there with his dog, Rosie, than go to middle school, where kids call him Sir Limps a Lot, McGimpster, or Uno—for his one good leg. What Zane doesn't know is that the volcano is a gateway to another world and he is at the center of a powerful prophecy. A new girl at school, Brooks, informs him that he's destined to release an evil god from the ancient Maya relic he is imprisoned in—unless she can find and remove it first. Together they return to the volcano, where all kinds of crazy happens. Brooks turns into a hawk, a demon attacks them in a cave, and Rosie gives her all while trying to protect Zane. When Zane decides to save his dog no matter the cost, he is thrust into an adventure full of surprising discoveries, dangerous secrets, and an all-out war between the gods, one of whom happens to be his father. To survive, Zane will have to become the Storm Runner. But how can he run when he can't even walk well without a cane?